2008
DOI: 10.1038/nsmb.1504
|View full text |Cite
|
Sign up to set email alerts
|

FANCI phosphorylation functions as a molecular switch to turn on the Fanconi anemia pathway

Abstract: In response to DNA damage or replication fork stress, the Fanconi anemia (FA) pathway is activated, leading to monoubiquitination of FancD2 and FancI and their co-localization in foci. Here we show that, in the chicken DT40 cell system, multiple alanine-substitution mutations in 6 conserved and clustered S/TQ motifs of FancI largely abrogate monoubiquitination as well as focus formation of both FancI and FancD2, resulting in loss of DNA repair function. Conversely, FancI carrying phospho-mimic mutations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
261
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 207 publications
(283 citation statements)
references
References 36 publications
12
261
1
1
Order By: Relevance
“…31,32 FANCI also possesses numerous S/TQ motifs, known ATM/ATR phosphorylation consensus sites, and mass spectrometry revealed that at least 5 of these sites are phosphorylated in human and mouse FANCI. 15,33,34 The alignment of human and chicken FANCI sequences revealed that 8 S/TQ motifs are highly conserved, with 6 of these motifs clustering proximal to K523, the site of FANCI monoubiquitination. 9,10,33 Importantly, the 3.4A crystal structure of the murine Fancd2-Fanci heterodimer (ID2) was recently solved by the Pavletich laboratory.…”
Section: Domain Architecture and Structure Of Fancd2mentioning
confidence: 99%
See 4 more Smart Citations
“…31,32 FANCI also possesses numerous S/TQ motifs, known ATM/ATR phosphorylation consensus sites, and mass spectrometry revealed that at least 5 of these sites are phosphorylated in human and mouse FANCI. 15,33,34 The alignment of human and chicken FANCI sequences revealed that 8 S/TQ motifs are highly conserved, with 6 of these motifs clustering proximal to K523, the site of FANCI monoubiquitination. 9,10,33 Importantly, the 3.4A crystal structure of the murine Fancd2-Fanci heterodimer (ID2) was recently solved by the Pavletich laboratory.…”
Section: Domain Architecture and Structure Of Fancd2mentioning
confidence: 99%
“…15,33,34 The alignment of human and chicken FANCI sequences revealed that 8 S/TQ motifs are highly conserved, with 6 of these motifs clustering proximal to K523, the site of FANCI monoubiquitination. 9,10,33 Importantly, the 3.4A crystal structure of the murine Fancd2-Fanci heterodimer (ID2) was recently solved by the Pavletich laboratory. While this structure continues to be a major resource for FA researchers, it is important to recognize that structural information remains lacking for several peptide stretches of both proteins.…”
Section: Domain Architecture and Structure Of Fancd2mentioning
confidence: 99%
See 3 more Smart Citations